The influence of thalamosinusotomy under different constant intraocular pressures on aqueous outflow facility in isolated porcine eyes - Mérula,Rafael Vidal (2008)
PURPOSE: To explorethe effect of the thalamosinusotomy ab interno, which is an experimental surgical procedure similar to sclerothalamotomy ab interno, on aqueous humor drainage. METHODS: Enucleated porcine eyes were perfused with Krebs-Ringer's physiologic solution and trypan blue, in vitro, under different constant pressures after the experimental procedure.The outflow facility and the stained/unstained tissue were measured. RESULTS: The outflow facility and the area under the curve (outflow) increased with the increasing number of thalamosinusotomy incisions (0 to 4). Thalamosinusotomy eyes showed more stained tissue (conjunctiva, outer sclera, inner sclera) than sham surgery eyes with significant statistical difference (P<0.05). CONCLUSIONS: The results suggested that outflow facility increases with the increasing number of thalamus, different pathways are stimulated after thalamosinusotomy, and the uveoscleral outflow could be an important route after the experimental surgical procedure.